Post-Translational Modification of PTEN Protein: Quantity and Activity - Li, Xiao; Yang, Pu; Hou, Xiaoli; Ji, Shaoping (Oncology Reviews, 2024)
Post-translational modifications play crucial roles in regulating protein functions and stabilities. PTEN is a critical tumor suppressor involved in regulating cellular proliferation, survival, and migration processes. However, dysregulation of PTEN is common in various human cancers. PTEN stability and activation/suppression have been extensively studied in the context of tumorigenesis through inhibition of the PI3K/AKT signaling pathway. PTEN undergoes various post-translational modifications, primarily including phosphorylation, acetylation, ubiquitination, SUMOylation, neddylation, and oxidation, which finely tune its activity and stability. Generally, phosphorylation modulates PTEN activity through its lipid phosphatase function, leading to altered power of the signaling pathways. Acetylation influences PTEN protein stability and degradation rate. SUMOylation has been implicated in PTEN localization and interactions with other proteins, affecting its overall function. Neddylation, as a novel modification of PTEN, is a key regulatory mechanism in the loss of tumor suppressor function of PTEN. Although current therapeutic approaches focus primarily on inhibiting PI3 kinase, understanding the post-translational modifications of PTEN could help provide new therapeutic strategies that can restore PTEN’s role in PIP3-dependent tumors. The present review summarizes the major recent developments in the regulation of PTEN protein level and activity. We expect that these insights will contribute to better understanding of this critical tumor suppressor and its potential implications for cancer therapy in the future.